2022
DOI: 10.3390/sym15010026
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue “Advanced Symmetry Methods for Dynamics, Control, Optimization and Applications”

Abstract: Nonlinear systems described by differential equations are of great theoretical significance and do frequently arise in practice [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Using the Lyapunov function, AII approach and Lambert W function, we have obtained the satisfactory FTISS properties. On the other hand, delay is an important factor to affect the stability, 37‐40 and so it is interesting for our future work to consider our results to the delay case.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Lyapunov function, AII approach and Lambert W function, we have obtained the satisfactory FTISS properties. On the other hand, delay is an important factor to affect the stability, 37‐40 and so it is interesting for our future work to consider our results to the delay case.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the widespread applications of time delay in various technical domains such as engineering technology, mechanics, cybernetics and biomedicine, the research scope of TDS has gained prominence among researchers. Specifically, comprehensive research on TDS stability revealed a critical issue pertaining to control theory, which has been assessed in various monographs [1][2][3][4][5][6][7][8][9][10][11][12][13]. For example, in [14], Zhao and Zhu discussed a neutral stochastic highly nonlinear time-delay system with a nonlinear growth condition.…”
Section: Introductionmentioning
confidence: 99%
“…Consider the following two-dimensional G-SDDE. Let ϕ 1 (t) = −0.05 + 0.1 sin(10t), ϕ 2 (t) = 0.05 − 0.1 sin(10t), τ(t) = 0.5 sin(t), ε = 1 and the corresponding coefficient matrices be as follows:[4,5], O 12 ∈ [1, 2], O 22 ∈[4,5] …”
mentioning
confidence: 99%